Studies on Transition Metal Impregnated Mx(lnGa)1_XN modulated structures for wide band gap multi-junction Solar cells. - Devarajan, Mutharasu (Universiti Sains Malaysia, 2013)
GaN and Ga-rich InGaN have been considered as the most important and indispensable materials used for the fabrication of efficient thin film solar cells which are active in entire visible and part of the near UV spectral regions. Initially, Al doped Ga203 thin film was synthesized using staking method and doping occurs at >400°C. Non-stoichiometry Al doped Ga203 thin film was observed by post annealing.